Switching from natalizumab to fingolimod: A randomized, placebo-controlled study in RRMS - Kappos, Ludwig (Neurology, 2015)
OBJECTIVE: To investigate the effect of different natalizumab washout (WO) periods on recurrence of MRI and clinical disease activity in patients switching from natalizumab to fingolimod. METHODS: In this multicenter, double-blind, placebo-controlled trial (TOFINGO), patients with relapsing-remitting multiple sclerosis (RRMS) were randomized 1:1:1 to 8-, 12-, or 16-week WO followed by fingolimod treatment over 32 weeks from last natalizumab infusion (LNI). Brain MRI was performed at baseline and weeks 8, 12, 16, 20, and 24. RESULTS: Of 142 enrolled and randomized patients, 112 (78.9%) completed the study (8 weeks, n = 41/50; 12 weeks, n = 31/42; 16 weeks, n = 40/50). Number (95% confidence interval [CI]) of active (new/newly enlarged T2) lesions from LNI through 8 weeks of fingolimod treatment (primary outcome) was similar in the 8-week (2.1 [1.7–2.6]) and 12-week WO groups (1.7 [1.3–2.2]) and higher in the 16-week WO group (8.2 [7.3–9.1]). During the WO period only, the number (95% CI) of active lesions increased with increasing WO duration (8 weeks, 0.4 [0.2–0.6]; 12 weeks, 2.1 [1.6–2.6]; 16 weeks, 3.6 [3.0–4.2]). Over the 24 weeks from LNI, gadolinium-enhancing T1 lesion counts were lower in the 8-week WO group (14.1 [5.67–22.53]) than in the 12-week (21.3 [1.41–41.19]) or 16-week (18.5 [8.40–28.60]) WO groups. More patients were relapse-free in the 8-week (88%) and 12-week (91%) WO groups than the 16-week WO group (84%). Sixty-eight percent of patients experienced adverse events (mostly mild/moderate), with similar incidence across groups. No unusually severe relapses or opportunistic infections occurred. CONCLUSIONS: Initiating fingolimod therapy 8–12 weeks after natalizumab discontinuation is associated with a lower risk of MRI and clinical disease reactivation than initiation after 16-week WO. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that for patients with RRMS switching from natalizumab to fingolimod, shorter natalizumab WO periods are associated with less MRI disease activity than are longer WO periods.